Perspectives on going from clinical work to research, and research where you work: Perspectives on meetings between research and clinical practice - Areskoug Josefsson, Kristina (Nordisk Tidsskrift for Helseforskning, 2021)
Research in practice is influenced by the knowledge and understanding that researchers and those who work in clinical practice have about each other’s point of view. Through common understanding, sharing of experiences and co-production, research projects can lead to sustainable improvement, but instead it is common that there is insufficient knowledge of each other’s roles and context. For example, how will the intended research design affect practice and how can the implementation of the research in practice be affected by the project? What has the highest priority - the research project or the practical work? In the same way that we discuss treatments and results with patients and techniques in the clinic, research activities in the clinic should be discussed.